Peranan Anggaran Biaya Produksi Sebagai Alat Bantu Pengendalian dalam Upaya Pencapaian Efektifitas pada PT Perkebunan Nusantara III Medan - Indah Ayu Lestari; Ova Novi Irama (Al-Buhuts, 2023)
PT Perkebunan Nusantara III Medan is a State-Owned Company (BUMN) where the company is engaged in plantations. This study aims (1) to determine the preparation of the production cost budget at PT. Nusantara Plantation III Medan. (2) To determine the effectiveness of production cost control at PT. Nusantara Plantation III Medan. (3) To determine the role of the production cost budget in supporting the effectiveness of production cost control at PT. Nusantara Plantation III Medan. This research uses a qualitative approach with a descriptive research type at PT Perkebunan Nusantara III Medan. The type of data used is quantitative data with primary and secondary data collection. Primary data includes interview data with informants and secondary data in the form of production budget data for PT Perkebunan Nusantara III Medan and data collection techniques through documentation, observation and interviews. The research results obtained are from 2020 to 2022. (1) The preparation of the budget at PT Perkebuann Nusantara III Medan has been carried out in accordance with adequate procedures. (2) The effectiveness of the use of the budget as a means of controlling the production costs of PT Perkebunn Nusantara III Medan has been running effectively because the realized value is smaller than the production cost budget. This shows a favorable condition (3) The production cost budget at PT Perkebunan Nusantara III Medan has provided a significant role in the process of controlling production costs. Because the production cost budget that has been set has fulfilled the functions and objectives of the budget.